Time‐varying synchronous cell ensembles during consummatory periods correlate with variable numbers of place cell spikes. Issue 7 (26th April 2018) - Yagi, Saichiro; Igata, Hideyoshi; Shikano, Yu; Aoki, Yuki; Sasaki, Takuya; Ikegaya, Yuji
Abstract: Spike rates of a hippocampal place cell are not constant and vary even when an animal visits an identical place field with nearly identical behavior. As one potential neurophysiological source underlying place cell spiking variability, we focused on the temporally fluctuating activity states of neuronal ensembles. Spike patterns of hippocampal neurons were recorded from rats performing a linear track task. Within a single consummatory period, similar sets of neurons were more frequently recruited in synchronous firing events, whereas different synchronized firing patterns of neuronal populations tended to be identified in different consummatory periods. A linear regression analysis indicated that the time‐varying activation patterns of neuronal populations during consummatory periods are correlated with the spike rates of a place cell within its place field during running. These findings suggest that place cell in‐field spiking is not only triggered by static inputs that represent external environments but also strongly depends on the time‐varying internal states of neuronal populations.